WeECG: a low-cost real-time wireless ECG for new born monitoring with error concealment. (24th January 2023) - Sadok, Djamel F.H.; Brooman, Daniele Wanderley; Ribeiro, Andrea Maria Nogueira Cavalcanti; Junior, Jacinaldo Balbino de Medeiros; Kelner, Judith; Moura, José Henrique Silva
This work designs a low-cost wireless HR monitoring device, WeECG, that also stores the data for subsequent analysis. Additional important design requirements include ease of use, baby comfort, support for mobility while insuring also a high level of signal integrity. We first developed a client server architecture using off-the-shelf components and a smartphone running the Android operating system. During the development of the communication module, we tested and compared two separate communication technologies: a popular ultra-low power wireless transceiver with embedded base-band protocols and a BLE communication module. WeECG presented a smaller measurement error when compared with the palpation method and a standard deviation of 0.4069 BPM when the peak interval algorithm was applied. We also examined packet loss and developed strategies to mitigate its effect, making it possible to safely transmit ECG signals. Finally, we also analyse the solution in terms of cost, size and energy consumption.